Effects and safety of rituximab in systemic sclerosis: an analysis from the European Scleroderma Trial and Research (EUSTAR) group - (:unkn) unknown (My University, 2015)
Objectives To assess the effects of Rituximab (RTX) on skin and lung fibrosis in patients with systemic sclerosis (SSc) belonging to the European Scleroderma Trial and Research (EUSTAR) cohort and using a nested case-control design. Methods Inclusion criteria were fulfilment of American College of Rheumatology classification criteria for SSc, treatment with RTX and availability of follow-up data. RTX-treated patients were matched with control patients from the EUSTAR database not treated with RTX. Matching parameters for skin/lung fibrosis were the modified Rodnan Skin Score (mRSS), forced vital capacity (FVC), follow-up duration, scleroderma subtype, disease duration and immunosuppressive co-treatment. The primary analysis was mRSS change from baseline to follow-up in the RTX group compared with the control group. Secondary analyses included change of FVC and safety measures. Results 63 patients treated with RTX were included in the analysis. The case-control analysis in patients with severe diffuse SSc showed that mRSS changes were larger in the RTX group versus matched controls (N=25; −24.0±5.2% vs −7.7±4.3%; p=0.03). Moreover, in RTX-treated patients, the mean mRSS was significantly reduced at follow-up compared with baseline (26.6±1.4 vs 20.3±1.8; p=0.0001). In addition, in patients with interstitial lung disease, RTX prevented significantly the further decline of FVC compared with matched controls (N=9; 0.4±4.4% vs −7.7±3.6%; p=0.02). Safety measures showed a good profile consistent with previous studies in autoimmune rheumatic diseases. Conclusions The comparison of RTX treated versus untreated matched-control SSc patients from the EUSTAR cohort demonstrated improvement of skin fibrosis and prevention of worsening lung fibrosis, supporting the therapeutic concept of B cell inhibition in SSc.
Effects and safety of rituximab in systemic sclerosis